Incidence of Venous Thromboembolism in Families with Inherited Thrombophilia - Simioni, Paolo; Sanson, Bernd-Jan; Prandoni, Paolo; Tormene, Daniela; Friederich, Philip W.; Girolami, Bruno; Gavasso, Sabrina; Huisman, Menno V.; Büller, Harry R.; ten Cate, Jan Wouter; Girolami, Antonio; Prins, Martin H. (Thrombosis and Haemostasis, 1999)
The risk of spontaneous or risk-period related venous thromboembolism in family members of symptomatic carriers of antithrombin (AT), protein C (PC) or protein S (PS) defects, as well as of the Factor V Leiden mutation is still undefined. We performed a retrospective cohort study in family members (n = 793) of unselected patients with a documented venous thromboembolism and one of these deficiencies to make an estimate of this risk. The annual incidences of total and spontaneous venous thromboembolic events in carriers of AT, PC or PS defects (n = 181) were 1.01% and 0.40%, respectively, as compared to 0.10% and 0.04% in non-carriers, respectively (relative risks both 10.6). In carriers of Factor V Leiden (n = 224), the annual incidences of total and spontaneous venous thromboembolism were 0.28% and 0.11%, respectively, as compared to 0.09% and 0.04% in non-carriers, respectively (relative risks 2.8 and 2.5). Additional risk factors (immobilisation, surgery and trauma; oral contraceptive use; and pregnancy/ post-partum) increased the risk of thrombosis in carriers of AT, PC and PS defects as compared to non-carriers (relative risks 8.3, 6.4 and 8.2, respectively). Oral contraceptive use and pregnancy/ post-partum period increased the risk of thrombosis in carriers of Factor V Leiden to 3.3-fold and 4.2-fold, respectively, whereas other risk factors had only a minor effect.These data lend some support to the practice of screening family members of symptomatic carriers of a AT, PC and PS deficiency. For family members of symptomatic carriers of Factor V Leiden, screening does not seem to be justified except for women in fertile age.